Survival cost sharing among altruistic full siblings in Mendelian population - Garay, József; López, Inmaculada; Varga, Zoltán; Csiszár, Villő; Móri, Tamás F. (BMC ecology and evolution, 2024)
Background We focus on Haldane’s familial selection in monogamous families in a diploid population, where the survival probability of each sibling is determined by altruistic food sharing with its siblings during starvation. An autosomal recessive-dominant or intermediate allele pair uniquely determines the altruistic or selfish behavior, which are coded by homozygotes. We focus on the case when additive cost and benefit functions determine the survival probability of each full sibling. Results We provide conditions for the existence of the altruistic and selfish homozygote. We show that the condition of evolutionary stability of altruism depends on the genotype-phenotype mapping. Furthermore, if the offspring size increases then the condition of evolutionary stability of altruism becomes stricter. Contrary to that, for the evolutionary stability of selfish behavior it is enough if the classical Hamilton’s rule does not hold. Moreover, when the classical Hamilton’s rule holds and the condition of evolutionary stability of altruism does not hold, then the selfish and altruistic phenotypes coexist. Conclusions In summary, the classical Hamilton’s rule is a sufficient condition for the existence of altruism, but it alone does not imply the evolutionary stability of the pure altruistic homozygote population when the altruistic siblings share the cost of altruism.